NEPOTISME DALAM PERSPEKTIF HADIS: Suatu Kajian Hadis MauwdÃ»âÃ® - Sabir, Muhammad (Institut Agama Islam Negeri (IAIN) Palu, 2010)
This article deals with nepotism in the hadÃ®th perpective. Based on the takhrÃ®j al-ahÃ¢dÃ®th related to nepotism, their sub-theme, their number of mukharrij and their number of hadÃ®thÂ can be classified in detail as follows: the ahÃ¢dÃ®th on nepotism in ShahÃ®h al-BukhÃ¢rÃ® Â are 3 mutÃ»n al-hadÃ®th; in ShahÃ®h Muslim are 2 mutÃ»n al-hadÃ®th; in Sunan al-TurmÃ»dhÃ® Â is 1 matn hadÃ®th; in Sunan al-NasÃ¢âÃ® is 1 matn hadÃ®th; in Musnad Ahmad are 2 mutÃ»n al-hadÃ®th and in Mustadrak al-HÃ¢kim are 2 mutÃ»n al-hadÃ®th. Based on these findings, the number of hadÃ®th Â on nepotism are 11 mutÃ»n al-hadÃ®th and those ahÃ¢dÃ®th are found in the six-hadÃ®th references. However, of all the ahÃ¢dÃ®th found, none of them permitted to commit nepotism.Kata Kunci: nepotisme, takhrij hadis, syarah hadis